Teachers’ Experiences and Reflection on Social Networking Site: Application of Facebook on Students’ Learning - Acharya, Kamal Prasad; Acharya, Milan (Interdisciplinary Research in Education, 2022)
This paper explores the effect of the use of the social networking site 'Facebook' on students’ learning in public secondary schools in Nepal. It also examines the use of Facebook in teaching and learning to improve students’ academic performance. A mixed-method (QUAN-qual) research design with an opinionnaire survey tool was used to collect the quantitative data, whereas a semi-structured in-depth interview was used to collect qualitative data. One thousand teachers were selected randomly using the Raosoft sample size calculator with a 95% confidence level. The data from both these sources were analysed using SPSS software version 20 and thematically as well as verbatim methods. The study found that 69% of teachers used Facebook for other purposes than teaching and learning in public secondary schools. Also, 86% of teachers use Facebook during school hours which positively affects students’ academic performance. Based on this study, it is recommended that the use of Facebook need to be done only for academic purposes during school hours in the public secondary schools in Nepal.